Do Olive and Fish Oils of the Mediterranean Diet Have a Role in Triple Negative Breast Cancer Prevention and Therapy? An Exploration of Evidence in Cells and Animal Models - Donovan, Micah G.; Selmin, Ornella I.; Stillwater, Barbara J.; Neumayer, Leigh A.; Romagnolo, Donato F. (Frontiers in Nutrition, 2020)
Breast cancer is the most common malignancy and cause of cancer-related mortality among women worldwide. Triple negative breast cancers (TNBC) are the most aggressive and lethal of the breast cancer molecular subtypes, due in part to a poor understanding of TNBC etiology and lack of targeted therapeutics. Despite advances in the clinical management of TNBC, optimal treatment regimens remain elusive. Thus, identifying interventional approaches that suppress the initiation and progression of TNBC, while minimizing side effects, would be of great interest. Studies have documented an inverse relationship between the incidence of hormone receptor negative breast cancer and adherence to a Mediterranean Diet, particularly higher consumption of fish and olive oil. Here, we performed a review of studies over the last 5 years investigating the effects of fish oil, olive oil and their components in model systems of TNBC. We included studies that focused on the fish oil omega-3 essential fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) in addition to olive oil polyphenolic compounds and oleic acid. Both beneficial and deleterious effects on TNBC model systems are reviewed and we highlight how multiple components of these Mediterranean Diet oils target signaling pathways known to be aberrant in TNBC including PI3K/Akt/mTOR, NF-kB/COX2 and Wnt/beta-catenin.